212k views
4 votes
Which of the following equations shows how substitution can be used to solve the following system of equations?
(y = 2x - 7 \\ 3 * + 4y = 16A: 3(2x-7) + 4y = 16B: 3x + 4(2x-7) = 16 C: y = -7D: 3x + 4y = 2x - 7

1 Answer

4 votes

Answer:

B: 3x + 4(2x-7) = 16

Step-by-step explanation:

The system of equations is

y = 2x - 7

3x + 4y = 16

To solve the system of equations by substitution, we need to substitute the first equation on the second equation. Since y = 2x - 7, we will replace y by 2x - 7 on the second equation, so

3x + 4y = 16

3x + 4(2x - 7) = 16

Therefore, the answer is:

B: 3x + 4(2x-7) = 16

User Eduardomoroni
by
5.1k points